Caracterização biofísica e estrutural de criptídeos antimicrobianos: estudo da porção antigênica da proteína SmKI-1 de Schistosoma mansoni - Bruno de Paula Oliveira Santos (2021)
Antimicrobial drugs design is a study field that is extensive and diverse, as pathogenic microorganisms continue to cause serious health problems around the world, in addition to being able to become resistant to most drugs standardized in healthcare systems. In this thesis, we sought to identify antimicrobial peptides hidden in the sequence of a protein from the Schistosoma mansoni parasite. As a mechanism of action, it was hypothesized that the kunitz-type inhibitor SmKI-1 is cleaved from the tegument and would then be able to release membrane active peptides from its C-terminal domain. For this work, a pipeline was created to 1) identify the hidden peptides, named cryptids, through an in-house software; 2) evaluate the peptides, named schistocins, activity; 3) study their biophysical characteristics by in vitro and in silico experiments. In the first part, the enCrypted algorithm was used to perform proteolysis on SmKI-1 sequence and screen for potential antimicrobial activity. Schistocins were synthesized by solid phase platform, tested in vitro and evaluated by structural (CD, NMR) and thermodynamic (ITC) studies to investigate their structure-function relationship and to evaluate a peptide-membrane interaction. The enCrypted was able to predict AMPs in SmKI-1, with an accuracy of 87%. Biophysical analyzes describe a conformational change induced by zwitterionic and anionic membranes, moving from a random-coil-to-α-helices conformation and a peptide-membrane balance for all schistocins. The structural and dynamics data allow us to suggest a well-known mode of action of peptide-membrane interaction, in which the electrostatic attraction between cationic peptides and as anionic membranes results in bilayer disorder. In addition, NMR H/D exchange data with the largest observed entropy contribution to a peptide-membrane interaction is important as schistocins have different orientations on the membrane. This multidisciplinary approach makes sense of the best characteristics of these molecules and evaluates their potential. Finally, during the study process, a problem emerged whose solution was added to the thesis: adding terminals to peptides during structure calculation with two specific programs: CcpNMR Analysis 2.5 and Aria 2.3. This work demonstrates the robustness of the use of physical-chemical features of predicted peptides in the identification of new bioactive cryptids. In addition, the work shows a combination of these analyzes with biophysical methods to better understand peptide-membrane affinity and improve other algorithms.